2020
DOI: 10.14283/jfa.2020.55
|View full text |Cite
|
Sign up to set email alerts
|

Exploring associations between oral health and frailty in community-dwelling older people

Abstract: Background: In frail older people with natural teeth factors like polypharmacy, reduced salivary flow, a decrease of oral self-care, general healthcare issues, and a decrease in dental care utilization contribute to an increased risk for oral complications. On the other hand, oral morbidity may have a negative impact on frailty. Objective: This study explored associations between oral health and two frailty measures in community-dwelling older people. Design: A cross-sectional study. Setting: The study was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 23 publications
(24 reference statements)
2
34
0
1
Order By: Relevance
“…Based on these findings, poor oral health status is associated with physical frailty 10 . Previous studies have reported that oral health‐related factors associated with physical frailty include deterioration of oral function, such as reduced chewing ability and swallowing function, and periodontal disease 11‐15 . Moreover, xerostomia, which presents as a subjective feeling of oral dryness, has been reported to be associated with a greater likelihood of frailty 16,17 …”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on these findings, poor oral health status is associated with physical frailty 10 . Previous studies have reported that oral health‐related factors associated with physical frailty include deterioration of oral function, such as reduced chewing ability and swallowing function, and periodontal disease 11‐15 . Moreover, xerostomia, which presents as a subjective feeling of oral dryness, has been reported to be associated with a greater likelihood of frailty 16,17 …”
Section: Introductionmentioning
confidence: 97%
“…10 Previous studies have reported that oral healthrelated factors associated with physical frailty include deterioration of oral function, such as reduced chewing ability and swallowing function, and periodontal disease. [11][12][13][14][15] Moreover, xerostomia, which presents as a subjective feeling of oral dryness, has been reported to be associated with a greater likelihood of frailty. 16,17 Dry mouth is a common source of discomfort among older people and has negative physical and psychological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Oral health describes the “state of being free from mouth and facial pain, tooth infection and decay, tooth loss, and other diseases and disorders that limit an individual’s capacity in biting, chewing, smiling, speaking, and psychosocial wellbeing”(WHO, 2021). Poor oral health, such as dental caries and periodontal disease, negatively affects the cognitive and physical functioning of affected people (Everaars et al, 2021; WHO, 2021). Crucially, oral health problems are common among older persons because of a lifetime of exposure to socioenvironmental health determinants (Petersen & Ogawa, 2018; WHO, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Oral health is important, as multiple associations between oral health and general health exist. Inflammation in the oral cavity may disturb HbA1C levels in diabetes patients; oral inflammation may contribute to the manifestation of rheumatoid arthritis, and malnutrition and aspiration pneumonia are associated with poor oral health [ 5 , 6 , 7 , 8 , 9 , 10 ]. Oral health and inattention to oral hygiene by older people are associated with frailty and even mortality [ 2 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%